Integrating Information Services for Managing Regulations in International Maritime Transportation - Chlomoudis, Constantine; Kostagiolas, Petros A. (SPOUDAI Journal of Economics and Business, 2013)
Nowadays, decision making in maritime transportation includes information for obligatory or not regulations related to quality, safety and security. Decisions of this nature have a significant effect on the actual cost of quality, safety and security in maritime transport. Although regulatory information is important, it is rather fragmented due to the internationalized nature of maritime operations as well as because it involves various private and public sector standardization agencies. In that respect, the development of an integrated maritime information service is essential in order to reduce costs and in turn improve maritime transportation services, streamline the flow of commerce as well as aid in developing better international, regional and national schemes. This paper initially provides two methodologies for estimating the cost of quality/safety/security and thereafter discusses the importance of managing regulatory material and information. Thereafter, a review of the literature is taking place and some innovative initiatives are presented, e.g. the “Maritime Knowledge Centre” of International Maritime Organization (IMO). Finally, a rationale will be proposed for the development of an integrated information service in order to provide a suitable and reliable information-knowledge based framework for quality, safety and security in maritime transportation. The implications resulting from the development of such a framework is discussed together with its significance for managing the relevant information. JEL Classification: R41; L15; D83.